Court of Flowers (Union Oil Company)
No more beautiful spot may be found on Treasure Island, site of the Golden Gate International Exposition in San Francisco Bay, than the Court of the Flowers. In the foreground is the Girl and the Rainbow, beyond the Arc of Triumph and the Court of Reflections.